2019
DOI: 10.1002/gps.5099
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a brief Multicultural Cognitive Examination (MCE) for evaluation of dementia

Abstract: Background The aims of this study were to present the psychometric properties of a newly designed cognitive screening instrument, the Multicultural Cognitive Examination (MCE), and to compare it with the Rowland Universal Dementia Assessment Scale (RUDAS) in a multicultural population. Methods The study was a Western European cross‐sectional multicenter study. The MCE consists of four components evaluating separate cognitive functions and was constructed by adding measures of memory, verbal fluency, and visuos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
5
22
0
Order By: Relevance
“…This makes the RUDAS a valuable cross-cultural dementia screening instrument in clinical practice and in research. Studies have suggested that diagnostic accuracy of the RUDAS may be improved by adjusting raw scores in people with limited or no formal education (Nielsen et al, 2019c), by combining the RUDAS with informant report (Nielsen et al, 2016), or by adding other measures to the RUDAS to achieve a more comprehensive cognitive examination (Nielsen et al, 2019a). However, this needs to be further evaluated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…This makes the RUDAS a valuable cross-cultural dementia screening instrument in clinical practice and in research. Studies have suggested that diagnostic accuracy of the RUDAS may be improved by adjusting raw scores in people with limited or no formal education (Nielsen et al, 2019c), by combining the RUDAS with informant report (Nielsen et al, 2016), or by adding other measures to the RUDAS to achieve a more comprehensive cognitive examination (Nielsen et al, 2019a). However, this needs to be further evaluated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Several of such widely-applicable instruments have already been developed over the years across Europe, such as the aforementioned European Cross-Cultural Neuropsychological Test Battery (CNTB, Nielsen et al, 2018), the Multicultural Cognitive Examination (MCE, Nielsen et al, 2019), the Cross-Cultural Dementia Screening (CCD, Goudsmit et al, 2017), the computerized EMBRACED battery (Ibanez-Casas et al, in press), the computerized Battery for Neuropsychological Evaluation of Children (BENCI, Fasfous et al, 2015), an innovative verbal fluency-switching task (TFA-93, Narme et al, 2019) and a number of culturally -or regionally -appropriate picture-based memory tests, such as the Recall of Pictures Test (RPT, Nielsen et al, 2012), modified Visual Association Test (mVAT, Franzen et al, 2019), TMA-93 (Maillet et al, 2017), and TNI-93 (Maillet et al, 2016). A normative data and validation study was carried out for European majority groups, Pakistani/Indian, Polish, Turkish, and to a lesser extent Moroccan and Former yugoslavian participants for CNTB (using multilingual research assistants or trained interpreters); for the CCD, the normative data and validation study was conducted among native Dutch, Moroccan-Arabic, Moroccan-Amazigh (Berber), Turkish, Surinamese-Creole, and Surinamese-Hindustani participants (assessed by bilingual, bicultural neuropsychologists); a general multicultural immigrant population as well as native French individuals were studied for the normative data and validity studies of the .…”
Section: Eccron Supports the Use Of Widely Applicable Cross-cultural Tests As Opposed To Race-based Normsmentioning
confidence: 99%
“…2000a ; Rait et al. 2000b ) were used in the UK; the modified Visual Association Test ( Franzen et al., 2019 ), a literacy screener (unpublished), and the Stick Design Test ( Baiyewu et al., 2005 ) in the Netherlands; the computerized EMBRACED battery (unpublished) in Spain; the Cross-Linguistic Naming Test ( Ardila, 2007b ), the WHO/UCLA adaptation of the Rey Auditory Verbal Learning Test ( Maj et al., 1993 ), and the Multicultural Cognitive Examination ( Nielsen et al., 2019a ) in Denmark; and the TNI-93 ( Maillet et al., 2016 ), TMA-93 ( Maillet et al., 2017 ), TFA-93 ( Narme et al., 2019 ), and Montreal Cognitive Assessment ( Nasreddine et al., 2005 ) in France.…”
Section: Resultsmentioning
confidence: 99%